Determining the Exposure Pathway and Impacts of Microcystis on Threadfin Shad, Dorosoma petenense, in San Francisco Estuary. (21st February 2020) - Acuña, Shawn; Baxa, Dolores; Lehman, Peggy; Teh, Foo‐Ching; Deng, Dong‐Fang; Teh, Swee
Abstract : Using a novel approach, the dietary exposure of microcystin to threadfin shad, Dorosoma petenense, during the presence of the Microcystis spp. bloom in the upper San Francisco Estuary was validated using multiple lines of evidence, and thus there is a risk of toxicity through ingestion of Microcystis spp. CVP = Central Valley Project. Abstract: Blooms of the cyanobacterium Microcystis spp. could affect fish health through the ingestion of colonies as well as exposure to dissolved microcystins in the water column. The goal of the present study was to evaluate the dietary exposure pathway through which Microcystis spp. blooms may affect liver function and nutritional status using a novel approach involving multiple analytical methods to assess the potential risk. Our study was conducted using threadfin shad, Dorosoma petenense, which is a pelagic fish commonly exposed to Microcystis spp. blooms in the upper San Francisco Estuary. The approach incorporated published and optimized methods that offer multiple lines of evidence including in situ hybridization, immunohistochemistry, histopathology, condition factor indices, and nutritional profiles. Measurements of threadfin shad health and tissue condition were conducted at sites where Microcystis was present or absent during the 2007 bloom season. The results showed that dietary exposure to fish from Microcystis blooms resulted in the accumulation of microcystin in the gut and liver tissues of threadfin shad collected from the sites with blooms. Although toxicity endpoints were likely confounded by antecedent conditions, our findings demonstrate dietary exposure of Microcystis toxins to fish using a novel approach with multiple lines of evidence. Environ Toxicol Chem 2020;39:787–798. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.